Hubungan stres dan personaliti, tingkahlaku devian dan teori koping di kalangan pelajar sekolah menengah daerah Johor Bahru - Elamurugan, Puvarasi (2013)
The purpose of this studies are to identify different types of issues that are related to stress such as personality, deviant behavior and coping theories among the low achievers which is being increasing by day by nowdays. Around 342 respondents has been chosed from SMK Tasek Utara (2), SMK St. Joseph dan SMK Sri Rahmat. The students from form 1 form 2 and form 4 was selected for this research to evaluate the objective of this research. Some sets of questionnaire been given to the respondents to answer the research questions. SPSS version 17.0 was been used to analyse the data. The research findings show that, the students more frequently stress up when they have a lot of work load. Hence, students have to be smarter in dividing their time equally, so that can complete their work without any difficulties and stress.